Efficacy of a specific model for cognitive-behavioral therapy among panic disorder patients with agoraphobia: a randomized clinical trial - King, Anna Lucia Spear; Valença, Alexandre Martins; Melo-Neto, Valfrido Leão de; Freire, Rafael Christophe; Mezzasalma, Marco André; Silva, Adriana Cardoso de Oliveira e; Nardi, Antonio Egidio (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: Cognitive-behavioral therapy is frequently indicated for panic disorder. The aim here was to evaluate the efficacy of a model for cognitive-behavioral therapy for treating panic disorder with agoraphobia. DESIGN AND SETTING: Randomized clinical trial at Instituto de Psiquiatria da Universidade Federal do Rio de Janeiro. METHODS: A group of 50 patients with a diagnosis of panic disorder with agoraphobia was randomized into two groups to receive: a) cognitive-behavioral therapy with medication; or b) medication (tricyclic antidepressants or selective serotonin reuptake inhibitors). RESULTS: Although there was no difference between the groups after the treatment in relation to almost all variables with the exception of some items of the Sheehan disability scale and the psychosocial and environmental problems scale, the patients who received the specific therapy presented significant reductions in panic attacks, anticipatory anxiety, agoraphobia avoidance and fear of body sensations at the end of the study, in relation to the group without the therapy. On the overall functioning assessment scale, overall wellbeing increased from 60.8% to 72.5% among the patients in the group with therapy, thus differing from the group without therapy. CONCLUSION: Although both groups responded to the treatment and improved, we only observed significant differences between the interventions on some scales. The association between specific cognitive-behavioral therapy focusing on somatic complaints and pharmacological treatment was effective among this sample of patients with panic disorder and the response was similar in the group with pharmacological treatment alone. CLINICAL TRIAL REGISTRATION NUMBER: NCT 01025908